1993
DOI: 10.1089/aid.1993.9.761
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Expression of HIV Envelope Glycoproteins Triggers Apoptosis in CD4 Cells

Abstract: The cytopathic effect of HIV-1 and HIV-2 in CD4+ lymphocytes has been shown to be associated with apoptosis or programmed cell death. Using different experimental conditions, we demonstrate here that apoptosis is triggered by cell membrane expression of the mature HIV envelope glycoproteins, gp120-gp41 complex, and their interaction with CD4 receptor molecules. Viral entry alone did not induce apoptosis but virus replication was required in order to produce the gp120-gp41 complex. Indeed, expression of the HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
111
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(115 citation statements)
references
References 65 publications
4
111
0
Order By: Relevance
“…This cell surface signalling is also a different mechanism to the one described by Groux et al (1992) where CD4 + T cells isolated from HIV-infected individuals, despite being mostly HIVnegative, were predisposed to undergo apoptosis and some did so when confronted with another immunological challenge such as superantigens. Our results are in agreement with the apoptosis mechanism presented by Laurent-Crawford and collaborators (Laurent-Crawford et al, 1993) where membrane expression of HIV envelope glycoprotein, or in our case productive viral infection, would trigger apoptosis. However, subsequent CD4 engagement by gpl20 in the context of an infected cell would be required according to our observations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This cell surface signalling is also a different mechanism to the one described by Groux et al (1992) where CD4 + T cells isolated from HIV-infected individuals, despite being mostly HIVnegative, were predisposed to undergo apoptosis and some did so when confronted with another immunological challenge such as superantigens. Our results are in agreement with the apoptosis mechanism presented by Laurent-Crawford and collaborators (Laurent-Crawford et al, 1993) where membrane expression of HIV envelope glycoprotein, or in our case productive viral infection, would trigger apoptosis. However, subsequent CD4 engagement by gpl20 in the context of an infected cell would be required according to our observations.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, cultured T cell clones are exquisitely susceptible to apoptosis. LaurentCrawford and collaborators have demonstrated that gpl20-gp41 heterodimer complex may be programming cell death in CD4 + lymphocytes (Laurent-Crawford et al, 1993). The expression of the env gene in the lymphoblastoid T cell line CEM was sufficient to induce apoptosis possibly by generating the multimerization of surface CD4.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-mediated death of productively infected CD4ϩ T cells in vitro has, however, been found to be independent of CD95/CD95L interactions (4 -6), and the possible involvement of other members of the TNF receptor family has not been explored. Several findings suggest that viral proteins encoded by HIV-1 (gp120 envelope glycoprotein, Vpr) may induce death of either infected or uninfected CD4ϩ T cells in productively infected CD4 T cell cultures (22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…Interestingly, both induction and prevention of apoptosis has been reported in specific cell lines infected with poliovirus (Tolskaya et al, 1995). Apoptosis has also been proven as a major cause of cytopathogenicity in some virus systems (Jeurissen et al, 1992 ;Laurent-Crawford et al, 1993 ;Levine et al, 1993 ;Hinshaw et al, 1994 ;Esolen et al, 1995). In addition, enhancement of cytosolic calcium can trigger the apoptotic response (Bowen, 1993).…”
Section: Discussionmentioning
confidence: 99%